AB0682 Correlation between Disease Activity and Cardiovascular Parameters in Patients with Ankylosing Spondylitis. (15th July 2016) - Atzeni, F.; Gianturco, L.; Bongiovanni, S.; Talotta, R.; Sarzi-Puttini, P.; Turiel, M.
Abstract : Background: As cardiovascular (CV) involvement is frequent in patients with rheumatic diseases, it is important to implement strategies of early diagnosis, treatment and follow-up and to understand the relationship between this complication and disease activity. Objectives: To investigate the correlations between the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and a series of conventional and unconventional CV markers in a group of patients with ankylosing spondylitis (AS). Methods: We studied 30 patients with AS diagnosed using the New York criteria (14 males and 16 females with a mean age of 53.07±10.73 years), all of whom underwent a standard echocardiographic examination, a carotid ultrasound study (including IMT and PWV assessment), and speckle tracking echocardiography (STE). Results: Our AS patients had impaired STE-measured LV myocardial longitudinal ɛ(median 19.83%, IQR 16.00–24.40% vs 21.46%, IQR 18.35–25.69%; p <0.05) and higher PWV (right: median 7.81 m/sec, IQR 7.03–8.45 m/sec vs 6.86 m/sec, IQR 6.42–7.99 m/sec; p =0.07: left: median 7.77 m/sec, IQR 6.97–8.38 m/sec vs 6.85 m/sec, IQR 6.28–7.88 m/sec; p =0.06) compared to healthy controls. Stepwise regression analysis revealed a weak correlation between BASDAI values and right (p=0.04) and left carotid PWV (p=0.05), whereas LV global longitudinal strain (GLS) assessed by means of STE very significantly correlated with disease activity (p=0.001). There was no correlation with common carotid IMT (cIMT) or ejection fraction (EF). Conclusions: PWV and (especially) GLS are very important markers of CV damage and may identify CV involvement in AS patients earlier than conventional indices such as EF or cIMT, furthermore the are a correlation between these markers and disease activity. However, these findings need to be confirmed in a larger series of patients. Disclosure of Interest: None declared